Internet Addiction and Depressive Symptoms Among High School Students: A Cross-Sectional Study - Ardiyanti, Yulia; Fauziah, Hesti Fathan Nurfais; Sulastri, Sulastri; Dwilestari, Fuji; Safira, Puspita Dinda; Yuliana, Alvi Ratna (Chakra Brahmanda Lentera Institute, 2026)
Background: Internet addiction has become an emerging public health concern among adolescents and has been associated with adverse mental health outcomes, including depressive symptoms. However, limited evidence is available regarding the association between internet addiction and depressive symptoms among Indonesian high school students. Therefore, this study examined the association between internet addiction and depressive symptoms among high school students. Methods: This analytical cross-sectional study, reported according to the STROBE guidelines, was conducted among 81 Grade XI students at a State Senior High School 1, Kendal Regency, Indonesia, from June to August 2025. Internet addiction was assessed using the Internet Addiction Test (IAT) and depressive symptoms were assessed using the the Patient Health Questionnaire-9 (PHQ-9). Data were analyzed using Spearman's rank correlation test. Results: Most participants were female (56.8%) and aged 17 years (58.0%). The mean IAT score was 47.52 ± 15.43, while the mean PHQ-9 score was 8.96 ± 5.64, indicating predominantly mild internet addiction and mild depressive symptoms. Internet addiction showed a moderate positive correlation with depressive symptoms (r = 0.512, p < 0.001). Conclusion: Internet addiction was positively associated with depressive symptoms among adolescents. These findings provide preliminary evidence that may inform future school-based digital wellness and adolescent mental health initiatives